IMPLEMENTASI TEORI BELAJAR KONSTRUKTIVISTIK DALAM PEMBELAJARAN IPS UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA DI SMP MUHAMMADIYAH 4 SAMBI - Hidayat, Danang Wahyu; Satiti, Elvina Mukti; Widiyatmoko, Wahyu (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
The low learning outcomes of students at SMP Muhammadiyah 4 Sambi class VIII B in social studies are the main and important problems faced by teachers. The purpose of this study was to apply constructivist theory to the learning outcomes of class VIII B SMP Muhammadiyah 4 Sambi in social studies subjects. The method used in this research is Classroom Action Research (CAR) which consists of two cycles and there are four stages in each cycle, namely 1) planning, 2) implementation, 3) observation, and 4) reflection. Data collection was carried out through interview and observation techniques. The results obtained from this study are that there is an increase in learning achievement from cycle I and cycle II in social studies subjects at SMP Muhammadiyah 4 Sambi class VIII B with the application of constructivist learning theory